Unique recurrence patterns of cervical intraepithelial neoplasia after excision of the squamocolumnar junction. Issue 5 (3rd July 2014) - Herfs, Michael; Somja, Joan; Howitt, Brooke E.; Suarez‐Carmona, Meggy; Kustermans, Gaelle; Hubert, Pascale; Doyen, Jean; Goffin, Frederic; Kridelka, Frederic; Crum, Christopher P.; Delvenne, Philippe
<x xml:space="preserve">Abstract</x> Recent studies have identified a putative cell of origin for cervical intraepithelial neoplasia (CIN) and cervical cancer at the squamocolumnar junction (SCJ) and suggest that these cells may not regenerate after excision (loop electrosurgical excision procedure). Our study addressed the impact of SCJ excision on the temporal dynamics, histologic and viral (human papillomavirus, HPV) characteristics of recurrent CIN. One hundred and thirty‐one consecutive patients treated by excision and attending follow‐up visits were enrolled. We compared recurrent and initial CIN with attention to excision margins, timing of recurrence, CIN grade, HPV types, p16 immunophenotype and SCJ immunophenotype. During the follow‐up period (up to 4 years), 16 (12.2%) recurrences were identified. Four (25%) were identified at the first follow‐up visit, closely resembled the initial CIN 2/3 in grade and HPV type and were typically SCJ marker positive [SCJ(+)], suggesting nonexcised (residual) disease. Twelve (75%) manifested after the first postoperative visit and all were in the ectocervix or in mature metaplastic epithelium. All of the 12 delayed recurrences were classified as CIN 1 and were SCJ (−). In total, 9 out of 11 SCJ (−) recurrences (82%) followed regressed spontaneously. Taken together, these results show that new lesions developing from any HPV infection are delayed and occur within the ectocervix or metaplastic epithelium. This markedly lower risk of CIN 2/3 after successful SCJ excision suggests that the removal of the SCJ could be a critical variable in reducing the risk of subsequent CIN 2/3 and cervical cancer.